Patients’ needs and expectations with regard to rheumatology nursing care: results of multicentre focus group interviews - van Eijk-Hustings, Yvonne; Ammerlaan, Judy; Voorneveld-Nieuwenhuis, Hanneke; Maat, Bertha; Veldhuizen, Conny; Repping-Wuts, Han (Annals of the rheumatic diseases, 2013)
Objective The contribution of rheumatology nurses to improved patient outcomes is increasingly recognised but more research is needed about the effects of interventions. The patient's role in deciding about healthcare quality is considered pivotal and therefore patients’ opinions and expectations should be directional in defining priorities for a research agenda. The objective of this study was to explore needs and expectations with regard to rheumatology nursing care in patients with chronic inflammatory arthritis (CIA). Methods Patients aged 18–90 years from three medical clinics in different regions in The Netherlands were invited to participate in focus group interviews. The interviews were transcribed verbatim and independently analysed by the authors. In a consensus meeting the emerging subjects were categorised into themes which were verified in a fourth interview. Results In total, 20 patients, mean age 57 years old, participated in the focus group interviews. The majority had rheumatoid arthritis and mean disease duration was 15 years. The focus group interviews revealed 12 subthemes that were organised into four main themes: education, self-management support, emotional support and well organised care. Additionally, patients considered opinions about ‘the personality of the nurse’ (eg, easy to talk to) to be important. Conclusions Patients with CIA mentioned that many problems have to be addressed when one is faced with having a rheumatic disease. The focus group interviews yielded valuable information about the care these patients need and expect. This information will direct future research with regard to rheumatology nursing care.